Pengaruh Metode Transplantasi Karang terhadap Tingkat Kelulushidupan Karang di perairan Pasir Putih Situbondo - Clara Cantika Raharto; Nirmalasari Idha Wijaya; Rudi Siap Bintoro (Universitas Hang Tuah, 2022)
Pasir Putih Waters Situbondo has beautiful coral reefs and is often used for diving activities. Due to the large amount of coral damage caused by the activities of tourists or divers, coral transplants were carried out in these waters. The Diving UKM of Hang Tuah University has carried out coral transplantation using the bioreeftek method and the shelf and substrate method while the community has carried out coral transplantation using the rack, net and substrate method. This study aimed to determine the effect of the coral transplantation method on the survival rate of corals. The data collection locations were divided into three stations with different transplantation methods, namely station 1 (bioreeftek method) and station 2 (shelf and substrate method). This research method used descriptive analysis to determine the relationship between coral transplantation method with coral survival rates and to determine the relationship between oceanographic parameters and coral survival rates. The results showed that the survival rate of corals at station 1 were 56%, station 2 was 89%, station 3 was 20%. They showed that the coral survival rate at station 2 with the shelf and substrate method had better results. The method had high shelf legs to avoid stirring the bottom of the waters by currents or waves so that the sediment did not reach the bottom of the shelf and made of iron, which is stronger and stronger.